Intention to purchase halal products among consumers - Nadiah Rus Liyana, Rusli (2015)
Demand for halal products had increased tremendously due to expansion of the Muslim population worldwide. This study intends to investigate factors such as attitude, subjective norms and perceived behavioral control that influence the intention to purchase halal products among consumer in Malaysia. Factors that lead to buying decision among consumer must be understood carefully in order to boost the growth of halal industry. Based on the multiple linear regression analysis, the perceived behavior control is significantly influenced the intention to purchase halal products while attitude and subjective norms are not significantly influenced the intention to purchase. The finding indicates that an individual are able to control their perception and the intention to purchase halal products. Therefore, marketers, retailers, and manufacturers have to build an effective strategy to satisfy this value among potential consumers in Malaysia.